Dipole-switch induced modification of the emissive response of carbon nanotubes. (20th October 2017) - Glaeske, M; Bluemmel, P; Juergensen, S; Setaro, A; Reich, S
Abstract: The interaction of carbon nanotubes with the molecular dipole switch spiropyran is expected to affect the optical response of the tubes. Until now, the need of anchor groups to immobilize the switches on the tubes has hindered the experimental observation of the effects of switching on the emission behavior of the tubes. Here we present spiropyran-carbon nanotube complexes obtained by micelle swelling. This method does not require any anchor nor sophisticated chemistry to warrant close tube-switch proximity. For the first time, we observe the shifts predicted theoretically and their effect on the tubes' excitation and emission energies.